The Post-Moden Subject. A Recovery of the Moral Subject after its Abandonmentin the Twentieth Century - Ibarra, Carlos Thiebaut (2001)
How have the conceptions of the subject in Contemporary Philosophy changed? There are four moments in this development: a) The ethical conception of enlightened subjectivity; b) the different suspicious altitudes of such project in the XIX and XX centuries; e) the follow-up of those suspicious altitudes in what is called the philosophies of "malaise" in the XX century; d) the new conceptual articulation at the end of the century. Why have these changes and processes occurred? A general interpretive hypothesis belonging to the realm of moral philosophy is suggested: n the realm of practical life we are oriented "forwards" and the subject has aperformative and projective attitude; this dimension becomes opaque when the interpretation of such practica! life is understood as the result or product (and is understood as moving backwards). In light of that hypothesis, the different ways in which the philosophies of suspicion and malaise are blind to the ethical subject are analized and it is claimed that they are. therefore.blind to the ways in which the Twentieth Century has built, against those philosophical interpretations. moral dimensions -as the rejection of damage and the imputation of responsibilities- to which only the last moment of the last century seems to do justice.